2019
DOI: 10.1101/2019.12.26.19015883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

To resect or not to resect? Unbiased performances of single and combined biomarkers in intra-operative corticography for tailoring during epilepsy surgery

Abstract: Objective:Signal analysis biomarkers, in an intra-operative setting, may be complementary tools to guide and tailor the resection in drug-resistant epilepsy patients. Unbiased assessment of biomarker performances are needed to evaluate their clinical usefulness and translation. We defined a realistic ground-truth scenario and compared the effectiveness of different biomarkers alone and combined to localize epileptogenic tissue. Methods:We investigated the performances of univariate, bivariate and multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…18,19 To date, none of the proposed connectivity measures reached the sensitivity and specificity of HFOs on a systematic and representative data sample. 20,21 Another approach is to quantify the level of complexity of physiological signals, because disease degrades the physiological function and therefore decreases signal complexity. 22 Costa et al 23 suggest a multiscale entropy measure, which was successfully used to localize the seizure onset zone (SOZ) in the dataset of 13 pediatric patients with focal cortical dysplasia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 To date, none of the proposed connectivity measures reached the sensitivity and specificity of HFOs on a systematic and representative data sample. 20,21 Another approach is to quantify the level of complexity of physiological signals, because disease degrades the physiological function and therefore decreases signal complexity. 22 Costa et al 23 suggest a multiscale entropy measure, which was successfully used to localize the seizure onset zone (SOZ) in the dataset of 13 pediatric patients with focal cortical dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, multiple studies reported altered connectivity patterns inside the EZ compared to the non‐EZ, suggesting functional connectivity as a promising new interictal biomarker 18,19 . To date, none of the proposed connectivity measures reached the sensitivity and specificity of HFOs on a systematic and representative data sample 20,21 …”
Section: Introductionmentioning
confidence: 99%